2018
DOI: 10.1039/c8ra06421k
|View full text |Cite
|
Sign up to set email alerts
|

Significantly improved piezoelectric performance of PZT-PMnN ceramics prepared by spark plasma sintering

Abstract: Improved d33 (412 pC/N), (553 pm V−1), Qm (583), ferroelectricity, and temperature stability were achieved in PZT-PMnN piezoceramics by SPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…It was found that there was a small peak in lowangle, and the ratio I 002 /I 200 is less than 1/2, indicating the two-phase state. The presence of peak splitting also confirms this state [16,17]. The coexistence of two phases promises a better piezoelectric performance.…”
Section: Resultssupporting
confidence: 63%
“…It was found that there was a small peak in lowangle, and the ratio I 002 /I 200 is less than 1/2, indicating the two-phase state. The presence of peak splitting also confirms this state [16,17]. The coexistence of two phases promises a better piezoelectric performance.…”
Section: Resultssupporting
confidence: 63%
“…The values obtained for the physical and electrical properties depend on the method of obtaining these materials. The most often used procedures used for the development of intelligent materials are conventional mixed oxides technique [4,5], B-oxides technique [6], two-step columbite method [7], sintering by hot pressing [8] and a relatively new technique spark plasma sintering (SPS) [9], etc. Compositions from complex systems based on lead titanate-zirconate solid solutions are conventionally sintered at high temperatures (higher than 1150 o C) for more than 1 hour.…”
Section: Introductionmentioning
confidence: 99%
“…[ 39–43 ] The piezoelectric effect‐based speech recognition, on the other hand, could be self‐powered but is often limited by narrow operating frequency ranges and complicated fabrication processes. [ 26,44 ] Emerging triboelectric nanogenerator provided a promising solution for self‐powered acoustic sensing based on the coupling effect of contact electrification and electrostatic induction. [ 32–38,45–47 ] However, waterproofness, wide frequency response range, and flexibility of these devices could not simultaneously be achieved, which needs further development.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43] The piezoelectric effect-based speech recognition, on the other hand, could be self-powered but is often limited by narrow operating frequency ranges and complicated fabrication processes. [26,44] Emerging triboelectric nanogenerator provided a promising solution for self-powered acoustic sensing based on the coupling effect of contact electrification and electrostatic…”
Section: Introductionmentioning
confidence: 99%